2020
DOI: 10.1186/s40478-020-00897-7
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes rescue neuronal health after cisplatin treatment through mitochondrial transfer

Abstract: Neurodegenerative disorders, including chemotherapy-induced cognitive impairment, are associated with neuronal mitochondrial dysfunction. Cisplatin, a commonly used chemotherapeutic, induces neuronal mitochondrial dysfunction in vivo and in vitro. Astrocytes are key players in supporting neuronal development, synaptogenesis, axonal growth, metabolism and, potentially mitochondrial health. We tested the hypothesis that astrocytes transfer healthy mitochondria to neurons after cisplatin treatment to restore neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 68 publications
0
80
0
1
Order By: Relevance
“…This suggests that the cisplatin is not lowering the mitochondrial membrane potential, which agrees with Kleih and colleagues who observed that ovarian cancer cells treated with cisplatin also maintained their mitochondrial membrane potential ( Cocetta, Ragazzi & Montopoli, 2019 ; Kleih et al, 2019 ). Similarly, English et al found that cisplatin-treated neuronal cells could maintain and restore their mitochondrial membrane potential through the uptake of cisplatin-resistant mitochondria from astrocytes ( English et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the cisplatin is not lowering the mitochondrial membrane potential, which agrees with Kleih and colleagues who observed that ovarian cancer cells treated with cisplatin also maintained their mitochondrial membrane potential ( Cocetta, Ragazzi & Montopoli, 2019 ; Kleih et al, 2019 ). Similarly, English et al found that cisplatin-treated neuronal cells could maintain and restore their mitochondrial membrane potential through the uptake of cisplatin-resistant mitochondria from astrocytes ( English et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…Under normal physiological conditions, bidirectional intercellular transfers of cellular materials via permanent cell fusion and temporal tunneling nanotube formations lead to tissue development and repair [ 17 , 18 , 19 ]. However, under pathological conditions such as viral infection, chronic inflammation, diabetes, and cancer, the intercellular transfers of biological materials (including chromosomal and extrachromosomal genetic materials, cellular organelles, viruses) via permanent and temporal cell fusions lead to de novo cell transformations and tissue heterogeneity, and thus to the development of drug resistance and disease progression [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Hypoxia, mechanical stress, chronic inflammation, cytotoxic stress, and oncometabolites associated with free radical formations are reported to potentiate intercellular membrane fusion events, and these conditions are often associated with the glioma microenvironment [ 14 , 20 , 21 , 22 , 23 , 27 , 35 , 44 , 45 , 46 , 47 ]. The mRNA-binding protein of ELAV-family HuR is a valuable biomarker of brain tumor progression [ 48 , 49 , 50 , 51 ] and is involved in the regulation of the key cell-signaling pathways responsible for the inflammatory glioma microenvironment, the hypoxia-related stress response, the transitions of classic and proneural glioma subtypes to the mesenchymal subtype, the metabolic stress, and the reactive oxygen species (ROS) generation associated with D-2HG oncometabolite production in low-grade gliomas harboring single alleles with IDH1-R132H/C/S mutations [ 52 , 53 , 54 , 55 ].…”
Section: Hur-dependent Cell-signaling Pathways Of Cell Fusion and mentioning
confidence: 99%
“…Similarly, English et. al found that cisplatintreated neuronal cells could maintain and restore their mitochondrial membrane potential through the uptake of cisplatin-resistant mitochondria from astrocytes (English et al 2020).…”
Section: Cisplatin Treatment Induced Apoptosis Without Significantly mentioning
confidence: 99%